Safety and immunogenicity of an indigenously developed tetanus toxoid, diphtheria toxoid, and acellular pertussis vaccine (Tdap) in adults, adolescents, and children in India - Hitt J Sharma; Sameer Parekh; Pramod Pujari; Sunil Shewale; Shivani Desai; Anand Kawade; Mandyam Ravi; Jitendra Oswal; Saji James; N. Mahantashetti; Renuka Munshi; Apurba Ghosh; et al. (Taylor & Francis Group, 2023)
Background This study assessed safety and immunogenicity of Serum Institute of India Pvt Ltd (SIIPL)'s tetanus toxoid (TT), diphtheria toxoid (DT), and acellular pertussis booster vaccine (Tdap). Research Design and Methods In this Phase II/III, multicenter, randomized, active-controlled, open-label study, 1500 healthy individuals, aged 4-65 years, were randomized to receive a single dose of SIIPL Tdap or comparator Tdap vaccine (Boostrix®; GlaxoSmithKlines, India). Adverse events (AEs) during initial 30 minutes, 7-day, 30-day post-vaccination were assessed. Blood samples were taken before and 30 days post-vaccination for immunogenicity assessment. Results No significant differences in incidence of local and systemic solicited AEs were observed between the two groups; no vaccine-related serious AEs were reported. SIIPL Tdap was non-inferior to comparator Tdap in achieving booster responses to TT and DT in 75.2% and 70.8% of the participants, respectively, and to pertussis toxoid (PT), pertactin (PRN), and filamentous hemagglutinin (FHA) in 94.3%, 92.6%, and 95.0% of the participants, respectively. Anti-PT, anti-PRN, and anti-FHA antibody geometric mean titers in both the groups, were significantly higher post-vaccination compared to pre-vaccination. Conclusions Booster vaccination with SIIPL Tdap was non-inferior to comparator Tdap with respect to immunogenicity against tetanus, diphtheria, and pertussis and was well tolerated.